2008
DOI: 10.1007/bf03327782
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and behavioral pre-treatment predictors of weight loss outcomes

Abstract: This study tested whether baseline behavioral and psychological variables predict weight and fat loss among overweight, non-obese individuals participating in a six-month calorie restriction trial. Participants (N=48) were randomly assigned to four groups, three of which included a calorie restriction program and one of which served as a healthy diet weight maintenance control. For the purposes of this study, data were analyzed only for participants assigned to the three calorie restriction groups (n=36). Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
15
1
1
Order By: Relevance
“…Although numerous determinants of weight loss have been proposed [5,13,21,24,25,26], the issue is not settled yet. The major findings of this study were that easily obtained measures such as body weight change throughout the programme and gender were successfully associated with the final weight loss outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous determinants of weight loss have been proposed [5,13,21,24,25,26], the issue is not settled yet. The major findings of this study were that easily obtained measures such as body weight change throughout the programme and gender were successfully associated with the final weight loss outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous variables thought to be associated with attrition during weight loss interventions have been studied. Most of the published studies reported that higher age, less episodes of depression, non-smoking status, higher levels of physical activity or exercise, weight loss expectations and gender were predictors of attrition [19,20,21,22], but still most of the variability is unaccounted for, leaving considerable uncertainty about the true causes. Thus, we aimed to identify the early pre-treatment characteristics as well as weight loss at the first weeks of the study that would be strong independent correlates of final weight loss outcome and attrition.…”
Section: Introductionmentioning
confidence: 99%
“…Teixeira et al 2004; Dalle Grave et al, 2004, 2005). Greater stress (Yass-Reed, Barry, & Dacey, 1993), depressive symptoms (Teixeira et al 2004; Clark et al, 1996; Anton et al, 2008), and weight loss expectations (Teixeira et al 2004; Dalle Grave et al, 2004, 2005; Jones, Harris, Waller, & Coggins, 2005) are psychosocial factors that have received some empirical support for their role in predicting attrition. In interviews with noncompleters, Grossi et al (2006) found that most attributed their attrition to “practical problems,” including problems at work or home, or a difficult commute to the treatment center.…”
Section: Introductionmentioning
confidence: 99%
“…The remainder of this review will concentrate on the results from the phase 1 study conducted at the Pennington Center. For 6 months, 48 men and women were randomized to one of four treatment groups (4,12,43,48,50,51,71,108). For the CR group, individuals were restricted to 75% (a 25% CR) of their weight maintenance energy requirements.…”
mentioning
confidence: 99%